Autopsy findings of miliary tuberculosis in a renal transplant recipient - Shergill, Khushdeep; Shelly, Divya; G, Manoj; Kumar, Ritu Ranjan (Autopsy and Case Reports, 2017)
Miliary tuberculosis is a lethal form of disseminated tuberculosis (TB), deriving its name from the millet-seed-sized granulomas in multiple organs. As TB still remains a leading cause of morbidity and mortality in India, its disseminated forms need to be diagnosed early to ensure more aggressive treatment at the earliest possible time. However, a considerable number of cases are missed ante-mortem. We discuss the case of a 32-year-old immunocompromised, non-HIV patient with an ante-mortem diagnosis of pulmonary TB. However, multiple organ involvement by Mycobacterium tuberculosis was demonstrated on autopsy. This case highlights the role of autopsy as a research and learning tool, and prudential clinico-pathologic correlation, which will improve clinical outcomes in the future